Investigations into modelling and assessment of theoretical profiles using capacitive sensor. (1st January 2013) - Murugarajan, A.; Samuel, G.L.
Current developments towards assessment of surface finish using the area averaging technique have gained attention in the field of automotive manufacturing. In particular, use of tiny non-contact sensors plays a vital role during in-situ and online monitoring and process control. In this work, an attempt has been made for using non-contact capacitive sensor for characterisation of different theoretical (periodic) profiles. The capacitive response model is developed to predict equivalent theoretical capacitive displacement profile and relate accurately to a measured surface finish of the profile. The proposed model is simulated to predict dimensional parameters of various theoretical profiles. Furthermore, the feasibility to relate the capacitive response to dimensional and non-dimensional parameters of the theoretical profile is studied. The developed model is validated with the different theoretical profiles. Further, the model is validated with experimentally processed theoretical profiles using measurement setup. The results show that the observed and predicted non-dimensional parameters are well agreed with model output and measured output results. Further, it can be applied in non-periodic profile measurement using a sensor.